Analisis Faktor-Faktor yang Mempengaruhi Kualitas Audit Internal: Studi pada Inspektorat Provinsi Maluku - Piter Arson Welay (MAKSIMUM, 2020)
This study aims to test empirically the effect of competence, independence, work experience and internal control systems. using 61 samples of employees who work as auditors in the inspectorate of Maluku Province, Ambon City and West Seram Regency, the data analysis method uses SEM-PLS with the help of the WarpPLS 6.0 application. The results show that competence has no effect on audit quality, this is because the demographics of respondents have competencies that are not in accordance with the standards, so that in the last few years they have received a fair with exception audit opinion. Independence has a positive effect on audit quality, auditors who are always objective in carrying out the audit process will produce quality audits. Work experience has a positive effect on audit quality, the more experienced the auditor, the easier it will be to detect audit problems. The internal control system is able to strengthen the relationship between competence, independence and job satisfaction on audit quality, this shows that a good internal control system will support the creation of a quality audit.